2021
DOI: 10.1136/emermed-2020-210291
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of emergency calls and out-of-hospital cardiac arrest deaths during the COVID-19 pandemic: findings from a cross-sectional study in a UK ambulance service

Abstract: BackgroundIn response to the COVID-19 pandemic, a national lockdown was introduced on 23 March 2020. In the following weeks, emergency departments in the UK reported a reduction in attendances. We aimed to explore the incidence of emergency calls across North East England, as well as the number of out-of-hospital cardiac arrest (OHCA) deaths.MethodsData were collected for all patients who contacted North East Ambulance Service between 4 March 2019–2 June 2019 and 2 March 2020–31 May 2020 suffering stroke, ST e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 7 publications
1
13
0
Order By: Relevance
“…[1][2][3][4] Other EMS providers in the UK and North America observed initial decreases in call volumes. 5,6 Surges in demand in the second wave of the pandemic led to some ambulance services in the UK declaring major incidents and warning of care being compromised by overwhelming demand. 7,8 EMS call handlers in the UK are typically trained non-clinical staff who use either the Advanced Medical Priority Dispatch System (AMPDS) or NHS Pathways to triage what emergency care response is needed to calls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4] Other EMS providers in the UK and North America observed initial decreases in call volumes. 5,6 Surges in demand in the second wave of the pandemic led to some ambulance services in the UK declaring major incidents and warning of care being compromised by overwhelming demand. 7,8 EMS call handlers in the UK are typically trained non-clinical staff who use either the Advanced Medical Priority Dispatch System (AMPDS) or NHS Pathways to triage what emergency care response is needed to calls.…”
Section: Discussionmentioning
confidence: 99%
“…1-4 Other EMS providers in the UK and North America observed initial decreases in call volumes. 5, 6 Surges in demand in the second wave of the pandemic led to some ambulance services in the UK declaring major incidents and warning of care being compromised by overwhelming demand. 7, 8…”
Section: Introductionmentioning
confidence: 99%
“…The same evidence was also proved in different part of the world during the first pandemic wave. In Europe, data from Paris area [ 8 ▪ ] reported a 2-fold increase in OHCA incidence immediately before and during the weeks after Paris lockdown; similarly in England, both in London [ 9 ▪ ] and in North East England [ 10 ] where an increase in OHCA incidence strongly correlated with the daily number of COVID-19 cases was noticed in March–April 2020. Moving to America, an increase in OHCA during the first pandemic wave was pointed out not only in New York City, the most important USA outbreak of COVID-19 during the first wave, where a 3-fold increase in OHCA was highlighted [ 11 ▪ , 12 ], but in also in areas other than the United States of America [ 13 16 , 17 ▪▪ ], as in Canada [ 18 ] and in Brazil [ 19 ].…”
Section: Out-of-hospital Cardiac Arrest and Coronavirus Disease 2019mentioning
confidence: 99%
“…One of the most alarming and terrible factors concerning this topic is the dramatic reduction in the outcome of OHCA during the pandemic [ 8 ▪ , 9 ▪ , 10 , 11 ▪ , 13 , 17 ▪▪ , 23 ▪ , 27 , 29 , 30 , 31 ▪▪ , 36 , 42 ▪▪ , 43 , 55 , 56 , 57 ▪▪ , 58 ]. This affected all the outcomes commonly used for OHCA following Utstein recommendations [ 59 ], as the return of spontaneous circulation (ROSC), the survival at hospital admission and the survival at hospital discharge or at 30days, with and without good neurological outcome.…”
Section: Changing In Out-of-hospital Cardiac Arrest Patients’ Charact...mentioning
confidence: 99%
“…Importantly, most of these patients died without COVID-19 testing [2]. Data from the North East England Ambulance Service revealed that despite reduced incidence of emergency calls during the pandemic compared with 2019, there was a rise in the incidence of OHCA and OHCA deaths during the same period [3]. Also, Glober et al [4] observed increased OHCA incidence during the COVID-19 pandemic when compared with the prior year.…”
mentioning
confidence: 99%